Formação teórico-prática do professor alfabetizador em cursos Pedagogia da UFPA - SANTOS, Fernanda de Cassia Ribeiro dos (2023)
Considering the various aspects that have been emphasized in contemporary discussions about the training of literacy teachers, this research intends to analyze this training in the context of the Pedagogy courses offered by the Federal University of Pará (UFPA) in the different campuses located in the countryside. from the state of Pará. The general objective is to analyze the responses that the Pedagogical Projects of the Courses (PPCs) have given to the new requirements placed on the initial training of literacy teachers in view of the resizing of literacy understood as a broad, complex and multifaceted process of literacy. The research has a qualitative approach and uses methodological procedures typical of bibliographical, documentary and field research for the constitution of data. With regard to bibliographical research, the study was referenced in the following authors: Moraes (2012); Blacksmith (1996); Blacksmith and Teberosky (1986); Kleiman (2008; 1995); Soares (2003; 2004; 2009; 2010); Rua (1984), among others. The collection of documentary data was carried out on the websites of the different academic units/subunits of UFPA and followed the curricular components related to literacy and literacy, which make up the curricular matrix of the Pedagogy PPCs. In addition, an electronic questionnaire was applied to the directors of the courses in question in order to know the perceptions of these subjects about the problem addressed. The results reveal the existence of a very limited number of disciplines dedicated to literacy and literacy studies within the scope of PPCs, in addition to the absence of components that focus on multiliteracies. The directors emphasize the need to update the PPCs, incorporating contemporary concepts and approaches that broaden the perspectives of studies on literacy, as well as creating collaborative partnerships with educational networks, in order to improve the training of licensees.